Queen mothers : articulating the spirit of black women teacher-leaders - Jeffries, Rhonda B. 1965- (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
"Black women's experiences functioning as mothers, teachers and leaders are confounding and complex. Queen Mothers from Ghanaian tradition are revered as the leaders of their matrilineal families and the teachers of the high chiefs (Mùller, 2013; Stoeltje, 1997). Conversely, the influence of the British Queen Mother on Black women in the Americas translates as a powerless title of (dis)courtesy. Characterized as a deviant figure by colonialists, the Black Queen Mother's role as disruptive agent was created by White domination of Black life (Masenya, 2014) and this branding persists among contemporary perceptions of Black women who function as the mother, teacher, or leader figure in various spaces. Nevertheless, Black women as cultural anomalies were suitable to mother others for centuries in their roles as chattel and domestic servants in the United States. Dill (2014), Lawson (2000), Lewis (1977) and Rodriguez (2016) provide explorations of the devaluation of Black women in roles of power with these effects wide-ranging from economic and family security, professional and business development, healthcare maintenance, political representation, spiritual enlightenment and educational achievement. This text will interrogate contexts where Black women may function as Queen Mothers and contest the trivialization of their manifold contributions. Questions explored are: 1) How are Black women positioned to mother, teach and lead others in personal and professional spaces? 2) What are the experiences of Black women mothering, teaching and leading their own children, families, and communities? 3) How has spirituality influenced the leadership styles of Black women and mothers and teachers?"--